2015
DOI: 10.5194/gmd-8-1955-2015
|View full text |Cite
|
Sign up to set email alerts
|

<sup>GA</sup><i>SAKe</i>: forecasting landslide activations by a genetic-algorithms-based hydrological model

Abstract: Abstract. GA SAKe is a new hydrological model aimed at forecasting the triggering of landslides. The model is based on genetic algorithms and allows one to obtain thresholds for the prediction of slope failures using dates of landslide activations and rainfall series. It can be applied to either single landslides or a set of similar slope movements in a homogeneous environment.Calibration of the model provides families of optimal, discretized solutions (kernels) that maximize the fitness function. Starting fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The same coupling approach may be used with other recently proposed empirical models, such as GA-SAKe (Terranova et al, 2015).…”
Section: Stochastic Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The same coupling approach may be used with other recently proposed empirical models, such as GA-SAKe (Terranova et al, 2015).…”
Section: Stochastic Approachmentioning
confidence: 99%
“…Few examples of real-time predictions of the probability of triggering of rainfall-induced landslides in a small area (i.e., a slope or a small catchment) can be found in the literature (e.g., Sirangelo and Versace, 1996;Sirangelo and Braca, 2004;Schmidt et al, 2008;Greco et al, 2013;Capparelli et al, 2013;Terranova et al, 2015;Manconi and Giordan, 2016;Ozturk et al, 2016). This is due to the intrinsic difficulty of finding historical data sets of rainstorms and corresponding landslides occurring in a small area, with enough data to allow reliable estimation of the probability of landslide triggering during extreme (and thus rare) rainfall events.…”
Section: Stochastic Approachmentioning
confidence: 99%
“…As a way of investigating the amounts of rain deemed responsible for the observed types of ground effects, and considering the extent of the affected basins, the maximum amounts of UK cumulative rainfall in 24 h between t 1 and t 2 , h max (24), were also extracted for each cell of the domain. In fact, shallow landslides, flash floods and slope erosion commonly result strongly related to high intensity, short duration rainfall events (Cascini & Versace, 1986, 1988Terranova & Gariano, 2014;Terranova, Gariano, Iaquinta, & Iovine, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Terranova et al [25] developed a hydrological model based on genetic algorithms to predict landslide activations, showcasing its utility in forecasting and providing early warnings for civil protection. Similarly, Santangelo et al [26] demonstrated the efficiency of remote landslide mapping techniques using laser rangefinder binoculars and GPS, proving that geographical data gathered remotely is comparable to that collected through on-ground GPS surveys.…”
Section: Literature Reviewmentioning
confidence: 99%